Asymmetric Effects of Exchange Rates and Oil Prices on Inflation in Egypt - Kamara, Ahmed Mohamed; Sallam, Mohamed A. M.; Ebrahim, Ehab Ebrahim Mohamed (International Journal of Energy Economics and Policy, 2025)
This study aimed to examine the asymmetric effects of exchange rates and oil prices on inflation in Egypt using the nonlinear autoregressive distributed lag (NARDL) model. Relying on annual data during the period (1975-2023), the findings from the estimations in the long run show a negative impact of gross domestic product on inflation. While the money supply has a negative impact on inflation in both the long run and the short run, the asymmetric results indicate that positive changes in exchange rates lead to decreased inflation in both the long run and the short run, while negative changes in exchange rates result in increased inflation. Furthermore, both positive and negative changes in oil prices lead to increased inflation in the long and short run. From the study’s results, the main triggering factors of inflation in Egypt are instability in the exchange rate, oil prices, and money supply. Therefore, following a contractionary monetary policy is essential to tighten the money supply and avoid instability in the exchange rate market. Moreover, to curb inflation, the Central Bank of Egypt must ensure a stable exchange rate by attracting foreign private investment through macroeconomic policies that incentivize foreign investors.